How shared is decision‐making in multidisciplinary tumour conferences with patient participation? An observational study. (31st October 2022) - Schellenberger, Barbara; Heuser, Christian; Diekmann, Annika; Ernstmann, Nicole; Schippers, Anna; Geiser, Franziska; Schmidt‐Wolf, Ingo G. H.; Scholl, Isabelle; Ansmann, Lena
Abstract: Background: In some breast and gynaecologic cancer centres in Germany, patients participate in their own case discussion in multidisciplinary tumour conferences (MTCs), where treatment recommendations are discussed and finalized. However, the extent to which patients in MTCs are involved in decision‐making on treatment recommendations remains largely unexplored. Hence, this study investigates how recommendations are communicated to patients and the extent to which the interactions with patients in MTCs are in line with shared decision‐making (SDM). Methods: In this observational study, we audio‐recorded MTCs with patient participation in three breast and gynaecologic cancer centres in Germany. We qualitatively analysed the data with regard to content and linguistic aspects. Results: We analysed 82 case discussions. Recommendations made during MTCs were regarding (i) treatment options, (ii) treatment initiation, (iii) next (treatment) steps and (iv) whether a treatment method should be initiated at all. The decision about recommendations depended in part on patients' preferences or further course/further outcomes. Although the purpose of MTCs is to provide recommendations, some recommendations were framed as the final decision. The majority of the decision‐making conversation could be characterized as option talk (78%), during which patients were mostly proposed only one (treatment) option. Conclusions: This study establishes limited SDM in MTCs with patient participation. By indicating choices and thereby creating awareness of choices among patients, MTCs with patient participation could be used to foster SDM implementation. Patient or Public Contribution: Two representatives of a large self‐help organization for patients with breast cancer assisted the research project, particularly, in discussing the results.